2021
DOI: 10.3389/fmicb.2020.616692
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Major Sources of Water Contamination Using Machine Learning

Abstract: Current microbial source tracking techniques that rely on grab samples analyzed by individual endpoint assays are inadequate to explain microbial sources across space and time. Modeling and predicting host sources of microbial contamination could add a useful tool for watershed management. In this study, we tested and evaluated machine learning models to predict the major sources of microbial contamination in a watershed. We examined the relationship between microbial sources, land cover, weather, and hydrolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Mathematical models and bioinformatics tools 38 , e.g. using machine learning 60 , are needed to better understand the phenomenon of seasonal variation and the importance of microbial uptake in water bodies in the future. The research confirmed that data from the outflow can be a valuable source of information on the operation of wastewater treatment plants, but in order to create such models, more data needs to be collected from both activated sludge and the outflow, which has not been studied so far.…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical models and bioinformatics tools 38 , e.g. using machine learning 60 , are needed to better understand the phenomenon of seasonal variation and the importance of microbial uptake in water bodies in the future. The research confirmed that data from the outflow can be a valuable source of information on the operation of wastewater treatment plants, but in order to create such models, more data needs to be collected from both activated sludge and the outflow, which has not been studied so far.…”
Section: Resultsmentioning
confidence: 99%
“…We further evaluated ONN4MST for samples from the same biome but with different characteristics. Previous studies have reported that microbial community samples from the soil with different characteristics possessed high diversity [ 31 ]. To evaluate the capability of ONN4MST for predicting samples from the same biome with different characteristics, we introduced another cohort, about the seasonal changes of the Hadza people’s gut microbial communities [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Here we introduce DeepToA, an ensemble deep learning framework that aims at predicting the "theater of activity" (ToA) of a microbiome from the taxonomic and functional profiles of its metagenome. To the best of our knowledge, this is one of the first deep-learning approaches to focus on metagenomic data, rather than 16S community profile data, and to utilize both taxonomic and functional profiles (Shenhav et al, 2019;Zha et al, 2020;Wu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several deep-learning approaches have been developed to address microbiome-related questions, such as disease prediction (Oh and Zhang, 2020;Sharma and Xu, 2021), the annotation of antibiotic resistance genes (ARGs) (Li et al, 2021), microbial source tracking (Shenhav et al, 2019;Wu et al, 2021), and microbial community prediction (Thompson et al, 2019;Zha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation